Analysis of The Influence of Per Capita Income, Number of Family Dependents and Government Expenditures In The Education Sector On The Percentage of Child Labor Aged 15-17 Years In North Sumatra - Muhammad Ervin Sugiar; H. B. Tarmizi; Rujiman Rujiman (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2023)
Analysis of the Effect of Per Capita Income, Number of Family Dependents, and Government Expenditure in the Sector of Education on the Percentage of Child Labor Aged 15-17 Years in North Sumatra, Graduate School of the University of North Sumatra, 2020. The problem of child labor is an important issue that occurs especially in developing countries . The condition of child labor is related to poverty, income level, education level and other macro-economic indicators. This study aims to determine and analyze the effect of Per Capita Income, Total Family Dependents, and Government Expenditures in the Education Sector on the Percentage of Child Labor Aged 15-17 Years in North Sumatra. The data used is secondary data from 2017 – 2019 in North Sumatra Province. Source of data from the Central Bureau of Statistics of North Sumatra Province with tests carried out through classical assumption tests and statistical tests. With the help of the SPSS 24 program, the results of the data analysis show that the per capita income variable is negative and significant at α = 5 percent, the variable number of family dependents and government spending on education is not significant at α = 5 percent, to the percentage of child workers aged 15-17 year in North Sumatra. The regression results in the model are R-Squared = 0.264, which means that the independent variables used affect the dependent variable by 26.4 percent and the remaining 73.6 percent are influenced by other variables outside the model being analyzed.